System activities based on the use of visual materials for learning vocabulary in the english language. - Honores Ortega, Johan Patricio; Trejo Perea, Dayana Estefanía (Machala : Universidad Técnica de Machala, 2021)
The use of visual materials is particularly important for learning a new language. These types of materials have relevance during learning vocabulary in English. The following research work has a descriptive study where visual materials are analyzed during their use in learning vocabulary in English. For constructing the theoretical framework, it was needed bibliographical documentation that provides sound arguments to the research. Moreover, it was considered to develop a case study using an initial level student, who was predisposed to participate. The applied research methods were: participant observation, test and survey which helped with the data collection for the analysis and interpretation. As a result, the use of visual materials inside the classroom provided a meaningful learning to the student. Finally, it isrecommended to take visual materials into account when teaching English vocabulary as long as they are aligned to the content of the class, with the aim of improving the teaching-learning processes in students.
Keywords: LEARNING; VOCABULARY; ENGLISH